2018
DOI: 10.1080/13662716.2018.1475220
|View full text |Cite
|
Sign up to set email alerts
|

Chasing entrepreneurial firms

Abstract: Abstract:The search for a reliable dataset of entrepreneurial firms is ongoing. We analyze and assess longitudinal data on startups from two data sources-the National Establishment Time-Series (NETS) database and the Secretary of State (SOS) business registry data. Our primary purpose in this paper is to assess the usefulness and reliability of these two databases in measuring startup activity along a number of dimensions. Using the data to measure software startups, we conclude that data need to be carefully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The dataset has been widely used to answer empirical research questions. Related studies have looked at business survival (Choi et al, 2017), entrepreneurship (e.g., Echeverri‐Carroll & Feldman, 2019; Low et al, 2021), healthcare access (Tsui et al, 2020), industrial concentration (e.g., Dong et al, 2023; Rossi‐Hansberg et al, 2021; Zeballos et al, 2023), job creation (e.g., Neumark et al, 2006, 2011), and the local food environment (Berger et al, 2019; Schuetz et al, 2012). Although concerns had been raised by Crane and Decker (2019) about the ability of NETS to detect business trends for some industries, Zeballos and Marchesi (2022) showed that NETS is well suited to capture employment patterns similar to the County Business Patterns (CBP) for the grocery retail industry.…”
Section: Methods and Datamentioning
confidence: 99%
“…The dataset has been widely used to answer empirical research questions. Related studies have looked at business survival (Choi et al, 2017), entrepreneurship (e.g., Echeverri‐Carroll & Feldman, 2019; Low et al, 2021), healthcare access (Tsui et al, 2020), industrial concentration (e.g., Dong et al, 2023; Rossi‐Hansberg et al, 2021; Zeballos et al, 2023), job creation (e.g., Neumark et al, 2006, 2011), and the local food environment (Berger et al, 2019; Schuetz et al, 2012). Although concerns had been raised by Crane and Decker (2019) about the ability of NETS to detect business trends for some industries, Zeballos and Marchesi (2022) showed that NETS is well suited to capture employment patterns similar to the County Business Patterns (CBP) for the grocery retail industry.…”
Section: Methods and Datamentioning
confidence: 99%
“…The study finds that the county-level correlation of NETS employment and CBP employment is typically above 0.99. We follow the convention of Echeverri-Carroll & Feldman (2019) in omitting the last two years of data, which can be subject to revisions. Other studies using NETS and comparing it to administrative data counts include Neumark, Wall & Zhang (2011).…”
Section: The Geography Of Publicly-traded Companies' Establishmentsmentioning
confidence: 99%
“…The most widely cited limitations of the data set include the heavily imputed employment for smaller companies, adopting a broad view of employment (i.e., counting owners as employees), continuous data collection throughout the year (which can affect employment counts for businesses with a seasonal nature of operations as well as timing of the data), and multiyear gaps between actual business establishment and the establishment date reported by the NETS (Barnatchez et al, 2017; Echeverri-Carroll & Feldman, 2019).…”
Section: Data and Variablesmentioning
confidence: 99%